Research and Realization of the Simulation Test System for Train Control On-board Equipment - Research and Realization of the Simulation Test System for Train Control On-board Equipment (机车电传动)
Aiming at the requirement of simulation test to train control on-board equipment, the overall technical scheme and the realization method of the simulation test system for train control on-board equipment were presented by analyzing the running environment of the equipment. Through test application, it was proved that this system had comprehensive and effective simulation functions, and could provide complete and high-degree simulation test environment for on-board equipment in CTCS-0 level to CTCS-2 level train control system.